Sodium Oxybate Intolerance Associated with Familial Serum Acylcarnitine Elevation - Berner, Jon (American Academy of Sleep Medicine, 2013)
Our case describes clinical features of two families defined by joint phenotypes: sodium oxybate intolerance and elevated serum acylcarnitines. Oxybate intolerance variably presents as either cervical dystonia or sleep-related eating disorder. Our objective is to identify biological markers which predict a poor response to sodium oxybate as a treatment for disturbed sleep. Familial inheritance pattern, genotype analysis, multiorgan system involvement, and response to treatment suggest the presence of a secondary cause of fatty oxidation defect, i.e., mitochondrial disorder. Our case report supports the possible conclusion that variance in human mitochondrial metabolism may affect sodium oxybate tolerability. CITATION: Berner J. Sodium oxybate intolerance associated with familial serum acylcarnitine elevation. J Clin Sleep Med 2013;9(1):71-72.